Adverse effects of phenytoin and fosphenytoin. (October 2017) - Ferner, Robin E.
Abstract : Summary: Phenytoin (diphenylhydantoin) and fosphenytoin are still important treatments for seizure disorders. The experience of fosphenytoin suggests that many of the adverse effects recognized to occur with phenytoin can also occur with the newer pro-drug. Here we consider some of the more important adverse effects of these agents.